1997
DOI: 10.7556/jaoa.1997.97.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting epiglottitis: a protocol--the value of lateral neck radiographs

Abstract: A retrospective review was done on the medical records (March 1986 through December 1989) of patients referred to Pittsburgh Children's Hospital with the presumptive diagnosis of epiglottitis. Data obtained included age, final diagnosis, referring physician's radiographic evaluation/interpretation, procedures (intubation, IV administered, aerosol, cultures obtained), transport times, and long-term morbidity and mortality. The diagnostic value of lateral neck radiographs was analyzed. Lateral neck radiographs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Ragosta et al . retrospectively reviewed medical records and included child patients with possible/probable supraglottitis diagnosed by a physician . Seventy‐three children were reviewed and 59 children underwent lateral radiographs of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…Ragosta et al . retrospectively reviewed medical records and included child patients with possible/probable supraglottitis diagnosed by a physician . Seventy‐three children were reviewed and 59 children underwent lateral radiographs of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…5 H. influenza, Streptococcus pneumonia and H. parainjluenzae are the commonest organisms causing epiglottitis, closely followed by group A streptococcus which is increasing in incidence and accounts for 10% of all cases. 6 In this case the diagnosis was difficult. There was a past history of anaphylaxis, but as there was no facial oedema, inspiratory wheeze or rash, the diagnosis was unlikely.…”
Section: Discussionmentioning
confidence: 83%
“… 6 This feature is not always present, and Ragosta et al 6 reported a 33% specificity for lateral neck X‐rays in the diagnosis of epiglottitis. The rate at which an organism is cultured on throat swab varies from 50% to 70% of cases 6 . Blood cultures are positive in 25–90% of cases 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A lateral plain radiograph may be obtained and may show the thumbprint sign; however, lateral neck radiograph has little diagnostic value in the absence of competent personnel. A CT scan of the neck is extremely valuable in assessing not only the airway but also in differentiating acute epiglottitis from epiglottic abscess [12]. e primary goal in managing a patient with epiglottic abscess is securing the airway.…”
Section: Case Reports In Infectious Diseasesmentioning
confidence: 99%